Pakan Ikan Alternatif Berbahan Baku Lokal untuk Calon Induk Ikan Gurami (Osphronemus gouramy) - Sri Marnani; Taufik Budhi Pramono (Journal Omni-Akuatika, 2016)
The aims of this study was to get local raw material of feed fish  able to improve growth anddevelopment of gonads  and composition of the artificial feed and feed supplement that can improvethe reproductive performance of gouramy fish. The method used is the method of completelyrandomized. The research was used completly randomized design with four  treatments and fourrepetition. The treatmens tested were four kinds, pellet commercial (60%) additional sprouts mungbean (Phaseolus radiatus L), fruit peel papaya (Carica papaya) and cabbage (Brassica oleracea L) by40%, and a pelleted commercial (100%) as control. Absolute growth ranges from 6-425 g, the relativegrowth of 3.7 to 22.1%, the growth day 1-7,1 g / day, feed efficiency from 7.8 to 29.33%, GSI 0.1 to1.1% and HSI 0.8 to 1.7%. Temperatures ranging from 23- 31,5⁰C, pH 6.6 to 7.5, Oxygen 5.0 - 6.2ppm , ammonia  0 - 0.25 ppm. Supplemental feed mixture (40%) and commercial pellets (60%) canimprove the growth and reproductive performance brood gouramy. Results of measurement oftemperature, pH and ammonia still qualify live gouramy.Keywords : alternative fish feeds, brood, Osphronemus gouramy